Toxic Friendship and Hadith-Based Relational Ethics: A Thematic Study of Choosing Friends - Az Zahra, Fitria; Mugiyono, Mugiyono; Almunadi, Almunadi (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2026)
Toxic friendship has emerged as a significant relational problem in contemporary society, often marked by manipulation, imbalance, emotional harm, and the erosion of moral integrity. This article examines the ethical principles articulated in the Prophet Muhammad’s hadiths on choosing friends and explores their relevance for addressing harmful friendship patterns in the modern era. Using qualitative library research and a thematic hadith approach, the study draws on hadiths concerning friendship as primary sources and classical commentaries, including Fath al-Bari by Ibn Hajar al-Asqalani and Sharh Sahih Muslim by Imam al-Nawawi, as interpretive references. The analysis combines textual, contextual, and descriptive-analytical approaches to identify the ethical meanings embedded in these hadiths. The findings indicate that the hadith tradition emphasizes moral selectivity, social responsibility, self-protection, and relational balance as key principles for evaluating friendship. These values provide a normative framework for preventing and addressing unhealthy relationships that may harm psychological well-being, moral character, and spiritual integrity. The study concludes that hadith-based ethics of friendship remain contextually relevant for cultivating healthy, dignified, and morally responsible social relationships in contemporary life.